2017
DOI: 10.1063/1.4973342
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the structural properties of Zn-face and O-face single crystal homoepitaxial ZnO epilayers grown by RF-magnetron sputtering

Abstract: DC voltage fields generated by RF plasmas and their influence on film growth morphology through static attraction to metal wetting layers: Beyond ion bombardment effects

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
5
1
Order By: Relevance
“…a stronger band gap reduction is obtained by introducing GaN into ZnO than the opposite [90]. Furthermore, epitaxial ZnO can be achieved at relative low temperatures using magnetron sputtering [91], indicating that highly crystalline thin films may be easier to achieve, and thus more easy to scale up.…”
Section: Potential Of the (Znomentioning
confidence: 99%
“…a stronger band gap reduction is obtained by introducing GaN into ZnO than the opposite [90]. Furthermore, epitaxial ZnO can be achieved at relative low temperatures using magnetron sputtering [91], indicating that highly crystalline thin films may be easier to achieve, and thus more easy to scale up.…”
Section: Potential Of the (Znomentioning
confidence: 99%
“…This makes the use of ZnO particularly advantageous in the case of industrial applications where a large area has to be covered with a transparent electrode, as in the case of organic/inorganic solar cells and flat displays. Regarding these deposition techniques, detailed studies have reported, as an example, that films with a ω-scan full width at half maximum (FWHM ω ) of the 00.2 peak equal to 40-70 and 250 arcsec can be obtained by radio frequency (RF) sputtering on hydrothermally grown ZnO wafers (Zn face) 4,5 and by ALD deposition on GaN substrates, 6 respectively, using overall substrates temperatures 500 C. The low FWHM ω s obtained in the above-mentioned studies indicate layers of good crystal quality. In addition, they are within the range of values reported in the case of thin films grown by molecular beam epitaxy, chemical vapor deposition, and metalorganic chemical vapor deposition that are typically extending from 10 to 280 arcsec [7][8][9][10] (for a review see, as an example, Ref.…”
Section: Introductionmentioning
confidence: 99%
“…These misorientations and the block dimensions are assumed to be the key parameters affecting the x-ray peak profiles and are, therefore, extracted from the x-ray characterization. A similar approach, also previously employed in the case of RF-sputtered ZnO films, 4 appears to be the natural choice in the case of ALD-grown ZnO layers of high quality, considering that they generally present a c axis oriented residual columnar structure. 6,14 The purpose of the present study is to show that, despite exhibiting a residual columnar structure, the strain field introduced by dislocations with a screw component represents the main contribution to the ω-scan of the ZnO 00.2 reflection.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical stability, , catalytic properties, , and electronic properties , are dependent on the polarity. ZnO films have been fabricated by several techniques, such as sputtering, chemical vapor deposition (CVD), , molecular beam epitaxy (MBE), pulsed laser deposition, and liquid phase epitaxy . Solution-based methods are simple and environmentally friendly and can be used for the preparation of complex nanostructures at low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Epitaxial techniques are promising for optoelectronic applications. The homoepitaxial growth of ZnO single crystals and the effect of the substrate polarity have been investigated. For example, ZnO films grown by CVD were smooth and rough on the c (+)- and c (−)-surfaces, respectively . In the case of MBE, smooth surfaces were obtained on the c (+)- and c (−)-surfaces under different conditions. , Epitaxial growth in solutions is expected to be a simple method.…”
Section: Introductionmentioning
confidence: 99%